Some fixed point results in G-metric space involving generalised altering distances. (2018) - Gupta, Vishal; Saini, R.K.; Deep, Raman
In this paper, we proved fixed point results for the functions satisfying ϕ -contraction and mixed g-monotone property. We also give an example in support of our result.